Edukasi Pernikahan Dini Pada Remaja Di Desa Pandansari Kecamatan Paguyangan Kabupaten Brebes - Endang Susilowati; Rizha Yunia Lestari Dewi; Maryam Maryam (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
In Indonesia, the number of marriages is always increasing from year to year. In 2017 there were 1,936,934 residents who were married and the number increased to 2,016,171 residents in 2018 (BPS et al., 2020). In Pandansari village, as much as 76.6% of early marriage data. The purpose of conducting this research is to identify the causal factors and develop a critical understanding. This research method uses the ABCD (Asset-Based Community Development) method as an approach Community Service. As a result of this study, they do not have enough knowledge to thoroughly explain the causes and effects of early marriage. This element of ignorance is one of the main factors in the occurrence of early marriage, according to research by Muntamah et al., 2019.